ACTN3 genotype and swimming performance in Taiwan - Chiu, L.-L.; Wu, Y.-F.; Tang, M.-T.; Yu, H.-C.; Hsieh, L.-L.; Hsieh, S. S.-Y. (International Journal of Sports Medicine, 2011)
Studies have shown that the 577R allele of ?-actinin-3 (ACTN3) is more prevalent in sprint athletes than in the general population or in endurance athletes. We examined the distribution of ACTN3 R577X (rs 1815739) genotypes and alleles in the Taiwanese general population (603) and in elite sprint swimmers who had participated in international/national events (168). Additionally, 50 pre-adolescent (age 11-13 years) male students and 38 adult males who completed 12-weeks of swimming training, were included in the present study. We found that the frequencies of the R allele were significantly higher in female international sprint swimmers (67.6%) than in national sprint swimmers (50.0%) or in the general population (53.7%). The 25-m performance was significantly improved across the genotypes after swimming training among the pre-adolescent males but not among the adult males. In addition, pre-adolescents with the RR genotype had the best performance both before and after training although not statistically significant. In conclusion, the frequencies of ACTN3 577R allele were significantly higher in female international sprint swimmers than among national sprint swimmers or the general population. Furthermore, male pre-adolescents with either the ACTN3 RX or XX genotype showed a greater improvement in 25-meter swimming performance than those with the RR genotype.